MARITAL RAPE DALAM AL-QUR’AN:: Analisis Fungsi Interpretasi J.E Gracia dalam QS. Al-Baqarah (2): 222-223 dalam Tafsir Al-Azhar Karya Hamka - Rofiatul Windariana (IAIN Madura, 2022)
Marital rape is understood as an act of rape within a marriage. In Islamic law, the issue of coercion in sexual relations receives less attention due to the domination of patriarchy and a lack of understanding of religion, especially the existence of interpretations that are still gender-biased. The verse that is often used as legitimacy for ownership of women's bodies is Qs. Al-Baqarah (2): 222-223. Although this action has been given legal punishment in the legal system, analysis of this verse's interpretation is insufficient to become a starting point in producing the antithesis of an understanding that tolerates it. Through the interpretation function theory of Jorge J.E Gracia as a hermeneutical foundation, this study seeks to examine Hamka's relevant interpretation in Tafsir Al-Azhar to obtain alternative understandings that are relevant to today's context. Interpretation of Al-Azhar is considered relevant as a representation of interpretation which is closely intertwined with Indonesian sosial culture so it is possible to examine this phenomenon through different contexts of revelation and interpretation as well as the implications of the meanings of both related to the phenomenon of marital rape. Through this method, the conception offered by Hamka begins to focus on sosial aspects and shows significant differences between the context of revelation and the context of interpretation regarding the roles of husband and wife, as well as the relationship between the two.